The Influence of Process Parameters and Scanning Strategy on Lower Surface Quality of TA15 Parts Fabricated by Selective Laser Melting - Junjie Jiang; Jianming Chen; Zhihao Ren; Zhongfa Mao; Xiangyu Ma; David Z. Zhang (Metals, 2020)
With superior flexible manufacturing capability, selective laser melting (SLM) has attracted more and more attention in the aerospace, medical, and automotive industries. However, the poor quality of the lower surface in overhanging structures is still one of the factors that limits the wide application of SLM. In this work, the influence of process parameters and scanning strategy on the lower surface quality of SLMed TA15 (Ti-6Al-2Zr-1Mo-1V) titanium alloy parts were studied. The results showed that the laser surface energy density (EF) had a significant influence on the quality of the lower surface. Excessive EF led to obvious sinking of the molten pool and a serious slag hanging phenomenon. However, the too low EF easily contributed to the insufficient powder fusion in the lower surface area, which led to the agglomeration of a molten pool during core processing, resulting in slag hanging, pores, and powder spalling that reduced the quality of the lower surface. Moreover, the cross-remelting strategy and non-remelting strategy gained better surface quality at the low EF and high EF, respectively. In addition, it was found that the quality of the lower surface could be quickly and accurately evaluated by the cooling time of the molten pool during the processing of the lower surface. This research can increase the understanding of the forming mechanism of the lower surface and has certain guiding significance for the process optimization of the lower surface.